Numerical assessment of the side impacts on lithium-ion battery module integrated with honeycomb reinforcement - Mustaffa, Zahiraniza; Al-Qadami, Ebrahim Hamid Hussein; Topa, Ameen; Budiman, Bentang Arief; Mohd Hamka, Nur Aqila; Endrayana Dharmowijoyo, Dimas Bayu; Mohammad Razi, Mohd Adib (Elsevier, 2024)
Protection of lithium-ion batteries (LIB) from collision-related damage is a critical concern for electric vehicle (EV) manufacturers. However, predicting damage to the standard 18,650 LIB cells from external side impacts has received little attention. This study aims to numerically estimate the damage to the LIB pack attached to a Toyota Camry car model during a side impact at 32 km/h using a finite element approach. A honeycomb reinforcement design is proposed to mitigate side impact effects by adopting a special arrangement. The battery pack, consisting of 12 modules each with 417 LIB cells, was attached to the vehicle bottom in a “floor” configuration. Four scenarios were simulated, namely (i) baseline [no reinforcement, (S1)], (ii) LIB module with Aluminium Alloy 7075-T6 reinforcement (S2), (iii) LIB module with Stainless Steel 316L reinforcement (S3), and (iv) LIB module with Advanced High Strength Steel reinforcement (S4). Numerical results showed that among the 12 battery modules, only one suffered from significant damage in all scenarios. The maximum penetration for the baseline scenario was found to be 79.29 mm. The penetration was reduced by 22.4 %, 20.2 %, and 19.4 % after including the proposed reinforcement structure and using AHSS, AISI316L, and Al7075-T5 materials, respectively. The absorbed energy by the LIB cell component was reduced by around 0.5 MJ (i.e., 18.7 % reduction) when using the proposed reinforcement. The outcomes of this study showed the ability of the proposed reinforcement structure to mitigate the side impact effects on the LIB cells; however, further optimization studies using different materials and thicknesses are recommended.